Pupuk Organik Padat dari Eceng Gondok, Kotoran Sapi, dan Dedak Padi dengan Effective Microorganisme 4 (EM4) - Widyastuti, Sri; Arfa, Risa Suryananta (Al-Ard: Jurnal Teknik Lingkungan, 2021)
Water hyacinth (Eichonia crassipes) is one type of aquatic plant that has a fast growth rate. As a result, sunlight is blocked from entering the water, so that aquatic biota cannot carry out the photosynthesis process perfectly. This study aims to determine the value of C/N ratio, levels of Phosphorus (P), Potassium (K), pH, and temperature (T) in composting for 16 days with the addition of 200 mL of bioactivator effective microorganism 4 (EM4) in each reactor. Variations of raw materials used are Control Reactor (RK) containing 1.5 kg of water hyacinth; Treatment Reactor 1 (R1) contains 0.5 kg of water hyacinth + 1 kg of cow dung; Treatment Reactor 2 (R2) contains 0.5 kg of water hyacinth + 1 kg of rice bran; and Treatment Reactor 3 (R3) contains 0.5 kg of water hyacinth + 1 kg of cow dung + 1 kg of rice bran. The results showed that the combination of raw materials had an effect on the quality of the organic fertilizer produced. The combination of Treatment 3 (R3) produced organic fertilizer with the best quality, namely C/N ratio = 15.30%, pH = 7.16, macronutrient P = 4.91% and K = 8.36% which met the quality standard requirements. Minister of Agriculture Number 261/KPTS/SR.310/M/4/2019 concerning the minimum technical requirements for organic fertilizers, biological fertilizers, and soil improvement.